Controlling Adolescent Purchases: The Role of Authoritative Parenting in Reducing Impulsive and Compulsive Buying - Retno Mangestuti (Indonesian Psychological Research, 2025)
This study aimed to examine whether authoritative parenting reduces impulsive and compulsive buying in early adolescents. Using a quantitative correlational design, two separate analyses were conducted on a sample of 408 junior high school students (ages 12–15), divided into two groups. The first analysis assessed the relationship between authoritative parenting and impulsive buying, while the second examined its relationship with compulsive buying. the Authoritative Parenting Scale was used to measure authoritative parenting, while the Buying Impulsiveness Scale (BIS) and the Compulsive Buying Scale (CBS) were used to measure impulsive and compulsive buying, respectively. The results showed a negative and significant relationship between authoritative parenting and both impulsive (R = –.159, R² = .025, p = .023) and compulsive buying (R = –.219, R² = .048, p = .002). However, Fisher’s r-to-z test indicated no significant difference between the two effects (z = 0.59, p = .553). These findings suggest that authoritative parenting may protect adolescents from problematic buying tendencies and support early interventions targeting financial habits.